Implementation of Leading Program for Village Building Movement - Veronica Veronica; Entang Adhy Muhtar; Milwan Milwan (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
Implementation of main program is one of the benchmarks for the performance of local governments in achieving good governance. This study aims to determine the implementation of RT Bersih program and identify the supporting and hindering factors. The results of this study indicate that implementation of RT Bersih flagship program has been good, it can be seen from the organization that has been realized in organizational structure as well as the duties and functions, interpretation has been carried out through socialization and communication between implementers, suitability of application to work procedures in accordance with regulations as well as technical and implementing instructions and budget allocations are appropriate. Program socialization does not reach the community and condition of implementing officers who have other jobs are factors that can hinder the program, while supporting factors for RT Bersih program are clear organizational structure, availability of adequate human resources, conformity of program with technical and implementing guidelines. Implementasi program unggulan merupakan salah satu tolak ukur kinerja pemerintah daerah dalam mencapai good governance. Penelitian ini bertujuan untuk mengetahui implementasi program ‘RT Bersih’ serta mengidentifikasi faktor pendukung dan penghambatnya. Hasil penelitian menunjukkan bahwa implementasi program unggulan ‘RT Bersih’ sudah baik dapat dilihat dari organisasi telah diwujudkan dalam struktur organisasi serta tugas dan fungsi, interpretasi telah dilakukan melalui sosialisasi, komunikasi antar pelaksana, kesesuaian aplikasi terhadap prosedur kerja sesuai dengan peraturan serta petunjuk teknis dan pelaksana serta alokasi anggaran telah sesuai. Sosialisasi program tidak sampai kepada masyarakat serta kondisi petugas pelaksana yang memiliki pekerjaan lain merupakan faktor yang dapat menghambat program sedangkan faktor pendukung program ‘RT Bersih’ adalah struktur organisasi yang jelas, ketersediaan sumber daya manusia yang memadai, kesesuaian program dengan peraturan petunjuk teknis dan pelaksana.